Harmonization of Science and Religion as Problem Solving of Scientific Globalization and Humanitarian Crises - Ika Amiliya Nurhidayah (Averroes: Journal for Science and Religious Studies, 2024)
The development of science that has reached the global realm is currently in an unbalanced phase, the modern worldview that is actually able to harmonize science and religion actually refers more to the dominance of science, and sets aside religion, in this case Islam. UIN K.H Abdurrahman Wahid Pekalongan offers a new paradigm to overcome it, harmonization of science and religion. Therefore, the main focus of this research is how it works and its spelling in the academic world. To answer this problem, this study uses descriptive-qualitative methods. The results showed that the workings and implementation of harmonization of science and religion at UIN Gusdur as a problem solving scientific globalization and humanitarian crisis with the existence of scientific writing programs based on science and religion, Islamic education programs armed with technology, efforts to achieve international accreditation, multidisciplinary education, the establishment of science and religion-based study programs, the provision of Islamic courses in the early semesters, the KIP-K scholarship policy, and the development of Ma'had al-Jami'ah.